2021
DOI: 10.1590/1414-431x20209161
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of HCP5 inhibits cell proliferation, migration, and invasion through regulating EPHA7 by competitively binding miR-101 in osteosarcoma

Abstract: Patients with osteosarcoma (OS) usually have poor overall survival because of frequent metastasis. Long non-coding RNAs (lncRNAs) have been reported to be associated with tumorigenesis and metastasis. In this study, we investigated the expression and roles of lncRNA human histocompatibility leukocyte antigen (HLA) complex P5 (HCP5) in OS, aiming to provide a novel molecular mechanism for OS. HCP5 was up-regulated both in OS tissues and cell lines and high expression of HCP5 was associated to low survival in OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…After checking the full text of remaining articles, 28 studies were further excluded due to the reason of these studies without comparing the prognosis between high and low HCP5 expression or providing insufficient data for estimation of HR and 95% CI for survival rate or data from biographical analysis. Finally, nine literatures [ 13 , 15 20 , 26 , 27 ] coincided with the inclusion criteria were included in the present meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After checking the full text of remaining articles, 28 studies were further excluded due to the reason of these studies without comparing the prognosis between high and low HCP5 expression or providing insufficient data for estimation of HR and 95% CI for survival rate or data from biographical analysis. Finally, nine literatures [ 13 , 15 20 , 26 , 27 ] coincided with the inclusion criteria were included in the present meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The types of cancer in these studies included: non-small cell lung cancer, colorectal cancer, oral squamous cell carcinoma, clear cell renal cell carcinoma, gastric cancer, skin cutaneous melanoma and osteosarcoma. All included studies [ 13 , 15 20 , 26 , 27 ] evaluated the association between HCP5 expression levels and overall survival, the follow-up months ranged from 36 to 105. Five studies [ 13 , 15 , 16 , 19 , 26 ] reported the clinicopathological parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations